KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (Studi pada Mahasiswa STIEM Bongaya Makassar) - Orfiyanny S.Themba (Jurnal Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to know the simultaneous and partial influence between product quality, price, brand image and brand ambassador to purchase decision of Honda motorcycles. As quantitative research, a survey method using a questionnaire was used. The sampling technique was accidental sampling. The population in this research someone that were using Honda motorcycle, type BeAT, Scoopy and Vario in the Campus STIEM Bongaya. The sample was 97 respondents. Methods of data analysis usingisdescriptive analysis and multiple regression techniques. The results showed that the quality of products, price, brand image and brand ambassador influenced on purchase decisions of Honda motorcycles